Sequence analysis of the rDNA intergenic spacer of Metarhizium strains isolated in Brazil - Fabiana Y. Yanaka-Schäfer; Leonara P. Dall'Onder; Mariana C. Panichi; Roberta G. Mendes; Nelson J.R. Fagundes; Josiane B. Bandinelli; Maurício R. Bogo (Genetics and Molecular Biology, 2008)
To assess the extent of genetic variability of rDNA intergenic spacer (IGS) in Metarhizium sp., 34 strains (27 isolated in Brazil) were sequenced and analyzed together with an additional 20 Metarhizium anisopliae var. anisopliae sequences retrieved from GenBank. Overall, the global nucleotide diversity for the region under study was of 0.090, while for the Brazilian isolates it was only 0.016. Phylogenetic analyses showed four well-supported groups (A, B, C, and D), one of which (D) has not been previously identified. All but one of the Brazilian strains cluster in this novel D phylogroup, suggesting that the genetic variation found in Brazil is a subset of the worldwide M. anisopiliae var. anisopliae variation.